STATE OF THE ART ANALYSIS ON BATTERY-RELATED THREATS AND DEFENSES OF IOT DEVICES USING KITCHENHAM - Azka Ghafara Putra Agung; Aditya Pradana; Rahmat Budiarto (Jurnal Teknik Informatika (Jutif), 2024)
The Internet of Things (IoT) keeps growing in size every year, but its growth also companied with threats to its security. This paper centers on the research article that focuses on various attacks on IoT system and devices through power drain techniques targeting IoT devices. This paper discusses various existing attack models, and security model. The main objective is to reveal the state of the art of the security issues of IoT related to attacks to the devices’ power. The literature review is performed by implementing Kitchenham method and utilizing Google Scholar and Science Direct databases. 42 publications between 2010 and 2023, fulfilling the selection criteria are selected and comprehensively reviewed. To counteract power drain-induced Denial of Service (DoS) threats, the paper evaluates existing defense mechanisms specifically tailored to mitigate these attacks. These defenses encompass adaptive power management strategies, hardware-level security enhancements, and network-level security measures. The effectiveness, practicality, and trade-offs of these defense mechanisms are examined. The combination of these papers offers comprehensive insights into battery-related security concerns in the IoT landscape, with sleep deprivation attacks, Denial of Service-induced battery drain, and Vampire attack, highlighting the importance of robust security measures in the IoT ecosystem.